2009
DOI: 10.1080/10412905.2009.9700185
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Studies of Leaf Essential Oils of Three Species ofJuniperusFrom Tensift Al Haouz-Marrakech Region (Morocco)

Abstract: Volatile components from fresh and air-dried leaves of Juniperus thurifera var. africana, J. phoenicea and J. oxycedrus (Cupressaceae) were isolated by direct water distillation (Clevenger-type apparatus) and analyzed using GC (FID) and GC/MS. The essential oils from leaves of J. thurifera var. africana were characterized by a high sabinene content (16.5-21.8%), g-terpinene (9.3-11.5%), and a-pinene (7.6-9.1%). The major components for J. phoenicea were a-pinene (38.2-58%) and d-3-carene (7.6%), while 13-epi-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…Also, the yield of EOs from leaves of C. sempervirens L. obtained in this study was lower than that reported by Mazari et al (2010); Elansary et al (2012) and Amri et al (2013), and lower than the yield of EOs from cone of Tunisian C. sempervirens L. which reported by Ben Nouri et al (2015). The yield of EOs isolated from leaves of J. phoenicea L. obtained in this study was lower than that reported by Stasis et al (1996); Mazari et al (2010); Derwich et al (2010) and Amalich et al (2015), but it was relatively similar when compared to that reported by Angioni et al (2003) and Achak et al (2009). 2.…”
Section: Results and Discussion 1 Yield Of The Essential Oilscontrasting
confidence: 56%
“…Also, the yield of EOs from leaves of C. sempervirens L. obtained in this study was lower than that reported by Mazari et al (2010); Elansary et al (2012) and Amri et al (2013), and lower than the yield of EOs from cone of Tunisian C. sempervirens L. which reported by Ben Nouri et al (2015). The yield of EOs isolated from leaves of J. phoenicea L. obtained in this study was lower than that reported by Stasis et al (1996); Mazari et al (2010); Derwich et al (2010) and Amalich et al (2015), but it was relatively similar when compared to that reported by Angioni et al (2003) and Achak et al (2009). 2.…”
Section: Results and Discussion 1 Yield Of The Essential Oilscontrasting
confidence: 56%
“…The Barbary thuja, Tetraclinis articulata (Vahl) Masters, a member of the Cupressaceae family, is an endemic species of North Africa (Morocco, Algeria, and Tunisia). Outside this zone, we find small localities in southeastern Spain (Cartagena province) as well as Malta Island 1 . The surface area of Tetraclinis woodlands is estimated at 565 798 ha, which represents approximately 10% of the total forest cover in Morocco and the majority of the Moroccan Tetraclinis areas are more likely to be in the temperate and warm semi-arid bioclimatic zone.…”
Section: Introductionmentioning
confidence: 88%
“…The identification of the compounds was performed by comparing their retention indices and mass spectra with those found in the literature [10][11][12] and supplemented by the data system library of NIST. The relative proportions of the essential oil constituents were expressed as percentages obtained by peak area normalization, all relative response factors being taken as one.…”
Section: Component Identificationmentioning
confidence: 99%